Out of thin air? Apport studies performed between 1928 and 1938 by Elemér Chengery Pap - Nahm, Michael (Journal of Scientific Exploration, 2019)
Physical mediumship is characterized by the occurrence of phenomena that seem to defy currently prevailing standard theories of physics, such as movements of objects (macro-psychokinesis) and the seemingly unexplained materialisation of objects, sometimes in closed spaces (apports). Nevertheless, systematic investigations into apport phenomena have hardly been performed. The present article introduces one of the few exceptions. The studies were conducted by Elemér Chengery Pap from 1928 to 1938 in Budapest. He summarized his research in a voluminous but little known Hungarian treatise that ranks among the largest monographs of experimental parapsychology written by a single investigator. Still, his book contains descriptions of some the most spectacular occurrences recorded in physical mediumship. One medium in particular, Lajos Pap, allegedly produced apports that ranged from solid objects, various liquids, snow, plants, ensembles of living insects, crawfish, to living vertebrates up to the size of a sparrow hawk. After presenting an overview on the book’s contents and some of the most remarkable phenomena described therein, I summarize the results of an experimental series performed with Lajos Pap by another Hungarian-born researcher, Nandor Fodor. Drawing from Fodor’s and also other observations, I demonstrate that Chengery Pap’s research approach contained remarkable loopholes that devalue his effort to leave a supposedly objective report to posterity. The authenticity of Lajos Pap’s phenomena thus remains questionable. Nevertheless, Chengery Pap’s voluminous treatise remains of historical significance in parapsychology and provides an instructive example highlighting difficulties in studying physical mediums.